Exploration of Microbial Diversity and Community Structure of Lonar Lake: The Only Hypersaline Meteorite Crater Lake within Basalt Rock - Paul, Dhiraj; Kumbhare, Shreyas V.; Mhatre, Snehit S.; Chowdhury, Somak P.; Shetty, Sudarshan A.; Marathe, Nachiket P.; Bhute, Shrikant; Shouche, Yogesh S. (Frontiers in Microbiology, 2016)
Lonar Lake is a hypersaline and hyperalkaline soda lake and the only meteorite impact crater in the world created in the basalt rocks. Although culture-dependent studies have been reported, the comprehensive understanding of microbial community composition and structure of Lonar Lake remain obscure. In the present study, microbial community structure associated with Lonar Lake sediment and water samples was investigated using high throughput sequencing. Microbial diversity analysis revealed the existence of diverse, yet near consistent community composition. The predominance of bacterial phyla Proteobacteria (30%) followed by Actinobacteria (24%), Firmicutes (11%) and Cyanobacteria (5%) was observed. Bacterial phylum Bacteroidetes (1.12%), BD1-5 (0.5%), Nitrospirae (0.41%) and Verrucomicrobia (0.28%) were detected as relatively minor populations in Lonar Lake ecosystem. Within Proteobacteria, Gammaproteobacteria represented the most abundant population (21-47%) among all the sediments and as a minor population in water samples. Bacterial members Proteobacteria and Firmicutes were present significantly higher (p≥0.05) in sediment samples, whereas members of Actinobacteria, Candidate_division_TM7 and Cyanobacteria (p≥0.05) were significantly abundant in water samples. It was noted that compared to other hypersaline soda lakes, Lonar Lake samples formed one distinct cluster, suggesting a different microbial community composition and structure. The present study reports for the first time the different composition of indigenous microbial communities between the sediment and water samples of Lonar Lake. Having better insight of community structure of this Lake ecosystem could be useful in understanding the microbial role in the geochemical cycle for future functional exploration of the unique hypersaline Lonar Lake.